2009
DOI: 10.1016/j.bbr.2008.12.025
|View full text |Cite
|
Sign up to set email alerts
|

d-Cycloserine accelerates the extinction of cocaine-induced conditioned place preference in C57bL/c mice

Abstract: Recently, it was shown that d-cycloserine (DCS; a NMDA partial agonist) facilitated extinction of fear as well as cocaine conditioned place preference (CPP) in rats. Methods The present study examined the effects of DCS (15mg/kg i.p and 30 mg/kg i.p) on extinction and renewal of cocaine-induced CPP in C57bL/c mice. In parallel we examined the effects of DCS on locomotor activity. Results Extinction to cocaine CPP was significantly faster with DCS than with vehicle treatment (3 sessions, versus 6 sessions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 18 publications
5
62
1
Order By: Relevance
“…This persistent conditioned hyperactivity in the SRÀ/À subjects supports the conclusion that intact NMDA receptor signaling is critical to extinction learning. This genetic evidence builds upon pharmacological findings with augmented GMS activation (Paolone et al, 2009;Thanos et al, 2009;Myers and Carlezon, 2010) in models of drug-associated conditioning and suggests that NMDA receptor hypofunction may be a pathophysiological feature that increases susceptibility to addiction by inhibiting the extinction of conditioned behavior. Acquisition of behavioral sensitization was also affected by altered GMS activation, with the GlyT1À/ + subjects showing a hastened rate of acquisition and the SRÀ/À subjects showing a delayed rate.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…This persistent conditioned hyperactivity in the SRÀ/À subjects supports the conclusion that intact NMDA receptor signaling is critical to extinction learning. This genetic evidence builds upon pharmacological findings with augmented GMS activation (Paolone et al, 2009;Thanos et al, 2009;Myers and Carlezon, 2010) in models of drug-associated conditioning and suggests that NMDA receptor hypofunction may be a pathophysiological feature that increases susceptibility to addiction by inhibiting the extinction of conditioned behavior. Acquisition of behavioral sensitization was also affected by altered GMS activation, with the GlyT1À/ + subjects showing a hastened rate of acquisition and the SRÀ/À subjects showing a delayed rate.…”
Section: Discussionmentioning
confidence: 76%
“…Recent research has demonstrated that inhibiting presynaptic glutamate inhibitory autoreceptors, and thus augmenting glutamatergic synaptic neurotransmission, reduced craving in cocaine-addicted patients (Amen et al, 2011). Preclinical work with the GMS partial agonist Dcycloserine demonstrates that the selective potentiation of NMDA receptor signaling may be an effective means of enhancing extinction of drug conditioning (Paolone et al, 2009;Thanos et al, 2009;Myers and Carlezon, 2010), in a manner similar to the extinction of conditioned fear in agoraphobic patients (Ressler et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, most of what is known about the neural mechanisms of extinction learning was derived from studies that use aversive conditioning (e.g., footshock) or appetitive conditioning with natural rewards (e.g., food). The extinction of conditioned fear in both animals and humans [69][70][71][72][73][74][75][76][77][78][79][80] as well as a cocaine CPP [81][82][83] can be facilitated by the cognitive enhancing drug D-4-amino-3-isoxazolidone [D-cycloserine (DCS)], which is a partial agonist at the strychnine-insensitive glycine site of Nmethyl-D-aspartate (NMDA) receptors [84,85]. Nic Dhonnchadha and colleagues recently found that DCS enhances the extinction learning process and inhibits reacquisition of drug self-administration in rats trained to self-administer cocaine [86].…”
Section: The Neurobiological Substrates Of Extinction Learningmentioning
confidence: 99%
“…Facilitation of glutamatergic transmission enhances extinction of drug-seeking behavior [81,83,[186][187][188]. It is likely that additional neurotransmitter systems, including dopamine and acetylcholine, are also involved in the extinction of drug-cue/context associations [3,[189][190][191].…”
Section: Role In Extinction Learningmentioning
confidence: 99%